Transformation of Dowry from Traditional Practices to Maqashid Sharia: A Causal Analysis of Women's Dignity and Family Harmony - Fajar, Mokhammad Samson; Zaelani, Abdul Qodir (Universitas Islam Sultan Agung, 2025)
Marriage is a sacred institution in Islam that encompasses moral, social, and spiritual implications. The dowry, as an essential element of the marriage contract, has been prescribed to uphold the dignity of women and reinforce the foundation of the family. However, in social reality, the practice of dowry is often reduced to a mere symbol of formality or a burdensome customary obligation. This phenomenon illustrates the disconnect between the implementation of dowry and the objectives of Islamic law. This research employs a qualitative approach utilising normative-theological and sociological methods. Primary data were sourced from classical fiqh texts and al-Syāṭibi's seminal work (al-Muwāfaqāt), while secondary data were obtained from academic journals and customary marriage documents. This article adopts the framework of maqashid sharia and the principles of customary law (al-'ādah muḥakkamah), integrating perspectives from Islamic legal philosophy and cultural sociology theory to analyse the meaning of dowry both causally and contextually. The findings of the study indicate that the transformation of the concept of dowry from a customary symbol to a maqashid necessitates a reinterpretation of local values through a dialogue between tradition and the objectives of sharia. The dowry, restructured within the framework of maqashid sharia, contributes to the preservation of women's dignity, the strengthening of relational justice, and the enhancement of household harmony. This research presents the development of a maqashid causality analysis framework grounded in an Islamic social philosophy approach. Furthermore, it offers insights for both the community and policymakers to facilitate maqashid-based customary deliberation and enhance family law literacy. An extension of this research could involve an exploration of women's perceptions regarding the symbolic and strategic value of dowry within diverse Muslim customary communities.